Internalization of Religious Character Through the Teacher's Exemplary Method at Madrasah Aliyah Negeri 3 Jember - Nur Jannah; Roihana Nuronia (Journal of Islamic Education Research, 2023)
This research is motivated by the reality of the behavior of students who lack empathy, respect for teachers and parents, and impolite behavior both in words and actions at Madrasah Aliyah Negeri 3 Jember (MAN 3 Jember). Interestingly, the researchers found an implicit virtue competition, students' respect for anyone, and a basic form of exemplary. This situation attracted researchers to examine the internalization of religious character through the exemplary method of teachers at MAN 3 Jember. This research is qualitative research with a case study approach. The data sources are collected through interviews, observation, and documentation with descriptive analysis. The credibility test tests the validity of the data through the triangulation of sources, methods, and theories. This study draws the conclusion that the internalization of religious character through the teacher's exemplary method at MAN 3 Jember is carried out in stages, namely: providing understanding, getting used to policies, creating a good environment and interaction, providing good starting from the teacher, and demonstrating a role model. These five processes cannot be separated from the integration of good speech, actions, and attitudes following religious law. Madrasa policy is a gateway to habituation so that the responsibility is fulfilled to form good character, forming generations of Muslims who are faithful, knowledgeable, and have good morals towards Allah SWT and others.